ANALISIS PENGETAHUAN TENTANG PENCEGAHAN PENYEBARAN COVID-19 DENGAN KECEMASAN IBU MEMBAWA BAYI IMUNISASI DI KLINIK PRATAMA NINING PELAWATI - Fatwiany Fatwiany; Nailatun Nadrah; Rindi Fadila (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Corona virus disease (COVID-19) has an impact on health and health services, one of which is maternal anxiety in bringing babies for immunization, immunization is a specific passive effort (inserting bacterial or viral antigens of diseases that have been weakened or killed into the body to form antibodies (immune substances) against a disease. Due to immunization there is a decrease in immunization coverage. This study uses an analytical descriptive research design to analyze Knowledge About Prevention of the Spread of Covid-19 With Anxiety of Mothers Carrying Immunized Babies at the Pratama Nining Pelawati Clinic. The population in this study was all 35 mothers who have babies visited the nining clinic. The sample was taken using total sampling. The results showed that the majority of respondents had less knowledge about preventing the spread of Covid-19 when carrying immunized babies, namely 20 respondents (57 ,1%), 19 respondents (54.3%) respondents had severe anxiety when carrying immunized babies. statistical test, it can be seen that there is a relationship between knowledge about the prevention of the spread of Covid-19 and the anxiety of mothers carrying baby immunizations at the Nining Pelawati Pratama Clinic with p = 0.005 (p <0.05). It is hoped that midwives will cooperate with the COVID-19 task force in spreading correct information about the spread of COVID-19.